Natural Man - Moss, Arthur B., 1855- (Salt Lake City, UT : Project Gutenberg, 2013)
"Natural Man" by Arthur B. Moss is a philosophical discourse written in the late 19th century. This work delves into the origins of humanity, challenging religious narratives and presenting a case for the evolution of man from lower organisms. It emphasizes an empirical approach to understanding human nature and morality, positing that virtues are cultivated rather than instinctual. The book explores themes of evolution, morality, and the progress of civilization, arguing that man has progressed from a state of natural wickedness towards a more virtuous existence through rational thought and the application of reason. Moss critiques the theological explanations of existence and religion's role in society, suggesting that true advancement comes from secular understanding and individual effort. By tracing the development of humanity in various cultural contexts, he illustrates the ongoing struggles between primitive instincts and the pursuit of knowledge, ultimately advocating for a future guided by reason and enlightenment. (This is an automatically generated summary.)
Release date is 2013-09-15
Produced by David Widger
Keywords: Human beings -- Origin; Rationalism